Álgebra e formação docente : o que dizem os futuros professores de matemática - Pires, Flávio de Souza (Universidade Federal de São Carlos, 2012)
The main object of this study is the analysis of some speeches from a group of future Mathematics teachers from São Carlos, São Paulo State, in relation to algebraic language teaching in Basics Education. The question which led to the development of this research was to investigate what future Mathematics teachers say about the algebraic language in Basics Education based on their past and actual perception of their under graduation course. This qualitative research has foundation in an analytical-descriptive nature. The data collection was carry out by students group participation of Mathematics Degree from São Carlos, São Paulo State, whom had already taken part of an internship program in Basics Education. The data analysis was accomplished through future teachers written statements on a questionnaire disposed into categories. The mixed questionnaire was compounded by three distinct moments: the first involved some aspects concerning Algebra, Algebraic Thought and Algebraic Teaching; the second brought more specifically the movement of teacher s formation; and the third tried to identify the future teachers profile. From these statements we could identify some difficulties with algebra learning from future teachers since Basics Education, which was reinforced along academic life in Higher Education. Besides, we noticed future teachers worry about teaching when they compare scholar and academic algebra to their own learning experiences, indicating dissociation between them.
Keywords: Ensino superior; Educação matemática; Formação inicial; Ensino de álgebra; Álgebra Escolar e Álgebra Acadêmica; Scholar and Academic Algebra; Initial Mathematics teacher formation; Algebraic language teaching; Mathematics Education; CIENCIAS HUMANAS::EDUCACAO